PENERAPAN CTL BERBASIS BUDAYA MELAYU PADA PEMBELAJARAN MATEMATIKA DI KELAS VIII - Nurjehan, Rizki (Jurnal Pendidikan Guru, 2017)
This study aims to innovate the learning CTL with local culture. Implementation of Malay-based CTL is expected to help the application of learning CTL linking learning into students daily lives. Due to the culture synonymous with the daily life of students. This research resulted a device of CTL-based learning Malay. This study uses a model of development according to Thiagarajan, and Semmel Semmel 4-D models (four D models). Findings from the study: Device Learning CTL-based of Malay produced has met both criteria / invalid; 2) the effectiveness of the learning device of Malay-based CTL generated inferred based on: (i) Complete student learning classical trials I amounted to 79.41% and in the second test of 82.35%, (ii) the achievement active activity students and the ideal time of the trial I and II trials is ideal; iii) a positive response to the students learning activities at the component and the test I is 92.65% and in the second test of 95.92%, and (iv) management of teacher in the trials I and II are good.